Rising Star Exchange: An Alternative Capital Market for SME in Indonesia - Masripah .; Meizaroh .; Alvita Yuniar; Pramuditya Ardhana (President University Press, 2021)
The purpose of this paper is to formulate an ideal stock exchange to help Small-Medium Entity (SMEs) in getting the capital they need. SMEs face some difficulties to grow its business. Access to the capital market is one of their main obstacles. This research uses a descriptive approach. This research discusses the problem by using literature study and secondary data as a source of information which is then analysed to be interpreted. This paper analyses both equity crowdfunding and Indonesian Stock Exchange Acceleration Board as the currently available equity market for SMEs. The key takeaways from both capital markets then being used to develop a new capital market called Rising Star Exchange (RiSE). The results of this paper implicate that by having this stock exchange, SMEs will have better access to funding while the investors also get the level of protection they need. The paper contributes to the social, economic and business sciences. The results of this paper could be used by the government to formulate a regulatory environment which could support the growth of SMEs, by the SMEs to find another alternative source of fund, and by the investors to allocate their fund in SMEs investment.